Mujeres de Caño Indio Tibú - sustitución de cultivos de uso ilícito y seguridad alimentaria. - José Manuel Alba Maldonado; Javier Alonso Santiago Velásquez; Edidvanidt Jácome Garzón (Mundo Fesc)
This article aims to recognize the role of women in Caño Indio Tibú in food security within the framework of the illicit crop substitution process in 2017, using case studies, direct structured interviews, and participant observation as methods. In this regard, the families of Caño Indio Tibú are experiencing a food crisis due to two factors: one, the failure of the State to implement these measures, and two, the lack of subsistence crops on their farms. Likewise, the women of the Caño Indio village considered, based on their experiences and current conditions, that in order to carry out an illicit crop substitution process in Colombia, it is first necessary to guarantee autonomous food security processes for the families that access these substitution projects.